A comparison of treatment eligibility for hepatitis C virus in HCV-monoinfected versus HCV/HIV-coinfected persons in electronically retrieved cohort of HCV-infected veterans. - Butt, Adeel A; McGinnis, Kathleen; Skanderson, Melissa; Justice, Amy C (AIDS research and human retroviruses, 2011)
Treatment rates for hepatitis C virus (HCV) are low in actual clinical settings. However, the proportion of patients eligible for treatment, especially among those coinfected with HIV, is not well known. Our aim was to determine and compare the rates for HCV treatment eligibility among HCV and HCV-HIV-coinfected persons. We assembled a national cohort of HCV-infected veterans in care from 1998-2003, using the VA National Patient Care Database for demographic/clinical information, the Pharmacy Benefits Management database for pharmacy records, and the Decision Support Systems database for laboratory data. We compared the HCV-monoinfected and HCV-HIV-coinfected subjects for treatment indications and eligibility using current treatment guidelines. Of the 27,452 subjects with HCV and 1225 with HCV-HIV coinfection, 74.0% and 84.6% had indications for therapy and among these, 43.9% of HCV-monoinfected and 28.4% of HCV-HIV-coinfected subjects were eligible for treatment. Anemia, decompensated liver disease (DLD), chronic obstructive pulmonary disease (COPD), recent alcohol abuse, and coronary artery disease were the most common contraindications in the HCV, and anemia, DLD, renal failure, recent drug abuse, and COPD in the HCV-HIV-coinfected group. Among those eligible for treatment, only 23% of the HCV-monoinfected and 15% of the HCV-HIV-coinfected subjects received any treatment for HCV. Most veterans with HCV are not eligible for treatment according to the current guidelines. Even for those who are eligible for treatment, only a minority is prescribed treatment. Several contraindications are modifiable and aggressive management of those may improve treatment prescription rates.
Keywords: Adult; Antiviral Agents; Electronic Health Records; Eligibility Determination; Female; Hepatitis C, Chronic; HIV Infections; Humans; Male; Middle Aged; Registries; Veterans